XPG gene polymorphisms and glioma susceptibility: a two-centre case–control study. Issue 3 (3rd July 2021) - Yuan, L; Hu, WM; Chen, K; Shi, Q; Lin, A; Chen, HT; Zhuo, ZJ; Zeng, L
ABSTRACT: Background : Glioma, the most common tumour in children next to leukaemia, is difficult to treat, with a poor prognosis and high recurrence rate. Xeroderma pigmentosum group G (XPG) plays a key role in the nucleotide excision repair pathway, which may modulate individual susceptibility to developing cancer. We hypothesized links between XPG variants and glioma in children. Methods : We tested our hypothesis in a study comparing 171 glioma cases with 228 age and sex matched controls, determining XPG polymorphisms rs2094258 C > T, rs751402 C > T, rs2296147 T > C, rs1047768 T > C, rs873601 G > A by standard molecular genetic methods. Results : rs2094258 C > T was associated with a decreased glioma risk, but carrying the rs1047768 C or rs873601 A allele brought an increased risk. Subjects carrying 5 risk genotypes had a significantly increased glioma risk at an adjusted odds ratio of 1.97 (95% confidence Interval 1.26–3.08)(p = 0.003) when compared with those carrying 0–4 risk genotypes. Furthermore, children with 5 risk genotypes had a higher glioma risk when aged >60 months, were more likely to be male, and with subtypes of astrocytic tumours, and low-grade clinical stage, when compared to those with 0–4 risk genotypes. Preliminary functional exploration suggested that rs2094258 is linked with the expression of its surrounding genes in the expression quantitative trait locus analysis. Conclusion : Certain variants of XPG are risk factors for paediatric glioma, and so may be useful in early diagnosis.